REPRESENTASI MAKNA CINTA DALAM LAGU "MAYONAKA NO DOOR/STAY WITH ME" KARYA MIKI MATSUBARA - Dewi, Dian Candra; Pemayun, Pradnyani Putri; Maryanti, Dinda (Jurnal Pendidikan Bahasa Jepang Undiksha, 2023)
This research aims to describe the meaning of love in the song "Mayonaka no Door/Stay With Me" by Miki Matsubara and the use of the word “Ai” as a disclosure of love through the semiotic analysis of Roland Barthes. The research methods used are descriptive qualitative methods and analytical methods using Roland Barthes semiotic theory that examine the meaning of denotations, connotations, and myths. The results of a semiotic study of the song "Mayonaka no Door/Stay With Me" by Miki Matsubara is depicted in a woman who loves someone who used to be close to her, her lover. This is evidence in each verse of the lyrics of the song that explains the desire and longing with a man who became his lover. The woman gives her lover feelings of love and affection only. Until the time they had separated, the woman still remembered everything related to her lover.